2020
DOI: 10.1590/s1677-5538.ibju.2019.0367
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned after 20 years' experience with penile fracture

Abstract: Objective: To report our experience over the past 20 years in the diagnosis and surgical treatment of penile fracture (PF). Materials and methods: Between January 1997 and January 2017, patients with clinical diagnosis of PF were admitted to our facility and retrospectively assessed. Medical records were reviewed for clinical presentation, etiology and operative fi ndings. Postoperative complications, sexual and urinary function were evaluated. Results: Sexual trauma was the main etiological factor, responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 20 publications
3
32
0
4
Order By: Relevance
“…6 It is stated that urethral injuries are mostly accompanied by bilateral rupture. 3,7 The diagnosis of penile fracture is made clinically. Color doppler ultrasonography (USG) and/or magnetic resonance imaging (MRI) of the penis and perineum can provide useful information about the location and size of the fracture.…”
Section: Introductionmentioning
confidence: 99%
“…6 It is stated that urethral injuries are mostly accompanied by bilateral rupture. 3,7 The diagnosis of penile fracture is made clinically. Color doppler ultrasonography (USG) and/or magnetic resonance imaging (MRI) of the penis and perineum can provide useful information about the location and size of the fracture.…”
Section: Introductionmentioning
confidence: 99%
“…The role of imaging in patients with suspected PF is controversial with some authors assuming that PF is mainly a clinical diagnosis and should be treated surgically without delay (2)(3)(4). Others report good diagnostic accuracies for magnetic resonance imaging (MRI) and ultrasound (US) (5,6).…”
Section: Diagnostic Performance Of Mri and Us In Suspicion Of Penile ...mentioning
confidence: 99%
“…Generally, many authors emphasize the importance of prompt surgery for PF (2)(3)(4)10). In a meta-analysis, Amer et al found that surgery significantly improved outcome compared with conservative therapy (10).…”
Section: Patients Included In Statistcal Analysis (N=88)mentioning
confidence: 99%
See 2 more Smart Citations